Flexion following hip resurfacing and factors that influence it. - Grammatopoulos, G; Philpott, A; Reilly, K; Pandit, H; Barker, K; Murray, D; Gill, H (2012)
Flexion following arthroplasty of the hip is important for activities of daily living. Studies have highlighted a possible reduction in flexion following Metal-on-Metal Hip Resurfacing Arthroplasty (MoMHRA) but failed to account for inter-subject variability and the possible etiology for this reduction. This in vivo study aims to determine whether flexion is restored following MoMHRA and identify factors that influence it. Charnley Class A patients (n=112) that underwent MoMHRA were reviewed in a dedicated clinic assessing flexion (resurfaced and contra-lateral hips) and outcome. The difference in flexion between both hips was defined as flexion deficit (δflexion). Various patient (age, gender, BMI) and surgical (component orientation, size, head-neck-ratio, offset) factors were examined in terms of their effect on δflexion. MoMHRA-hips had significantly reduced flexion as compared to the native hips. This flexion-deficit correlated with contra-lateral maximum flexion, component size, head-neck-ratio and component orientation. The findings demonstrate that flexion following MoMHRA is strongly correlated to but is reduced in comparison to the native, disease-free, hip flexion. Surgical practice can minimise flexion-deficit and optimise function.